In situ insights into the nanoscale deposition of 5, 6-dihydroxyindole-based coatings and the implications on the underwater adhesion mechanism of polydopamine coatings. Issue 49 (3rd August 2018) - Lyu, Qinghua; Song, Hongyan; Yakovlev, Nikolai L.; Tan, Wui Siew; Chai, Christina L. L.
Abstract : The underwater in situ nano-deposition studies of 5, 6-dihydroxyindole (DHI) have provided new insights into the controversial deposition mechanism(s) of DHI-based and polydopamine-based coatings. Abstract : The biomimetic coating polydopamine (PDA) has emerged as a promising coating material for various applications. However, the mechanism of PDA deposition onto surfaces is not fully understood, and the coating components of PDA and its relation to the putative intermediate 5, 6-dihydroxyindole (DHI) are still controversial. This investigation discloses the deposition mechanisms of dopamine (DA)-based coatings and DHI-based coatings onto silicon surfaces by monitoring the nanoscale deposition of both coatings in situ using high-precision ellipsometry. We posit that the rapid and instantaneous nano-deposition of PDA coatings onto silicon surface in the initial stages critically involves the oxidation of DHI and/or its related oligomers. Our studies also show that the slow conversion of DA to DHI in PDA solution and the coupling between DA and DHI-derived precursors could be crucial for subsequent PDA coating growth. These findings elucidate the critical role of DHI, acting as an 'initiator' and a 'cross linker', in the PDA coating formation. Overall, our study provides important information on the early stage nano-deposition behavior in the construction of PDA coatings and DHI-based coatings.